SISTEM INFORMASI AKUNTANSI BIAYA STANDART PADA PT. INDONESIA ASAHAN ALUMINIUM (PERSERO) - Wesly Simanjuntak (JURNAL ILMIAH MAKSITEK, 2018)
In running an organization and implementing an internal control system, the role of the accounting information system is very important. The benefits of the accounting information system can be evaluated through its impact on increasing decision-making processes, the quality of accounting information, performance evaluation, internal control, and transactions that facilitate the company. Performance management is a business discipline that has a very fast maturity. Therefore, performance management has a key role in increasing the overall value of the organization.The formulation of the problem in this study is "Does the standard cost accounting information system function properly at PT. Indonesia Asahan Aluminum (Persero)? " While the hypothesis in this study is whether the standard cost accounting information system has not functioned well at PT. Indonesia Asahan Aluminum (Persero). The data collection process is carried out with library research and field research, the method of data analysis is done by qualitative data analysis methods.The results of this study are PT. Inalum has been very effective and efficient in carrying out its production activities, and also in providing raw materials needed for production activities, as well as in minimizing the costs associated with raw materials.The standard cost accounting information system carried out by the company looks good, where each activity must go through the procedures set by the company before.